Smart Islamic Education: Reconceptualizing the Integration of Digital Technology and Islamic Values - Zennanta Agustia; Azizah Intan Khoirotun Nisa'; Moh. Miftachul Choiri; Lailatun Nikmah (STIT Ahlussunnah Bukittinggi, 2026)
This article examines Smart Islamic Education as a conceptual framework for integrating digital technology and Islamic values in contemporary Islamic education. This study employs a qualitative approach through a systematic literature review to analyze scholarly works related to digital transformation, Islamic pedagogy, learning management systems, e-learning, blended learning, artificial intelligence, and digital ethics in Islamic education. The collected literature was examined thematically to identify emerging patterns, challenges, and opportunities in the implementation of technology-based Islamic education. The findings show that Smart Islamic Education should be understood as an integrative model that connects technology, pedagogy, and Islamic values in curriculum design, classroom interaction, institutional management, and digital culture. Its implementation is reflected in the use of learning management systems, interactive media, e-learning and blended learning, artificial intelligence, and the digitalization of educational governance. This model offers important opportunities for wider access, greater instructional efficiency, pedagogical innovation, stronger Islamic digital literacy, and more adaptive curricula, but it also faces major challenges related to infrastructure gaps, limited digital competence among educators, resistance to change, and the ethical risks of technology misuse.